Freedwomen and the Freedmen's Bureau : race, gender, and public policy in the age of emancipation - Farmer-Kaiser, Mary (Reconstructing America (Series), 2010)
Established in early 1865, the Bureau of Refugees, Freedmen, and Abandoned Lands - more commonly known as 'the Freedmen's Bureau' - assumed the task of overseeing the transition from slavery to freedom in the post-Civil War South. This book explains fully the Bureau's relationships with freedwomen, freedmen and black communities.